2023
DOI: 10.14348/molcells.2023.2157
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Functional MicroRNA Targeting

Abstract: MicroRNAs (miRNAs) play cardinal roles in regulating biological pathways and processes, resulting in significant physiological effects. To understand the complex regulatory network of miRNAs, previous studies have utilized massive-scale datasets of miRNA targeting and attempted to computationally predict the functional targets of miRNAs. Many miRNA target prediction tools have been developed and are widely used by scientists from various fields of biology and medicine. Most of these tools consider seed pairing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 158 publications
(221 reference statements)
0
7
0
Order By: Relevance
“…Numerous miRNAs have been found to have links to certain types of cancer [ 11 , 12 ]. Three observations made during the early stages of miRNA research suggested that they may play a role in human cancer.…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…Numerous miRNAs have been found to have links to certain types of cancer [ 11 , 12 ]. Three observations made during the early stages of miRNA research suggested that they may play a role in human cancer.…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…Moreover, miRNAs powerfully modulate various cellular activities such as cell growth, apoptosis, and differentiation (Saliminejad et al, 2019). It has also been shown that miRNAs play a key role in regulating biological processes and pathways, leading to significant physiological effects (Hwang, Chang, Baek, 2023). In addition, miRNAs exhibit abnormal expression levels in lung cancer and influence its initiation and progression (Li et al, 2022).…”
Section: Effects Of the Microrna-99a-5p/vldlr Axis In Lung Cancer Cel...mentioning
confidence: 99%
“…Most abundantly expressed small non-coding RNA better known as miRNA plays an important role in cancer progression by targeting subcellular proteins at post-transcriptional or -translational levels (Calin and Croce 2006 ; Hwang et al 2023 ). One of the most interesting features of a miRNA exhibited a context-dependency via regulating multiple targets even in the same cancer types (Genc et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%